Modyfikacje znaczenia i walencji związków frazeologicznych jako mechanizm frazeotwórczy - Ignatowicz-Skowrońska, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*65.77px); top: calc(var(--scale-factor)*174.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00034);" role="presentation">The article deals with the semantic and valence modifications of three phraseological <span dir="ltr" style="left: calc(var(--scale-factor)*66.35px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03374);" role="presentation">units: <span dir="ltr" style="left: calc(var(--scale-factor)*91.86px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.927963);" role="presentation">leżeć i <span dir="ltr" style="left: calc(var(--scale-factor)*118.35px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.929151);" role="presentation">kwiczeć, <span dir="ltr" style="left: calc(var(--scale-factor)*153.55px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.992989);" role="presentation">mieć na <span dir="ltr" style="left: calc(var(--scale-factor)*187.24px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.987142);" role="presentation">pieńku <span dir="ltr" style="left: calc(var(--scale-factor)*216.65px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05055);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*234.35px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.956137);" role="presentation">grać pierwsze skrzypce<span dir="ltr" style="left: calc(var(--scale-factor)*323.55px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.992804);" role="presentation">. Initially, these units <span dir="ltr" style="left: calc(var(--scale-factor)*66.04px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05436);" role="presentation">were connected with personal nouns only and appeared in the multi-word lexical <span dir="ltr" style="left: calc(var(--scale-factor)*66.35px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03136);" role="presentation">units <span dir="ltr" style="left: calc(var(--scale-factor)*88.72px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.930187);" role="presentation">ktoś leży i <span dir="ltr" style="left: calc(var(--scale-factor)*129.27px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.936253);" role="presentation">kwiczy <span dir="ltr" style="left: calc(var(--scale-factor)*158.62px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.980758);" role="presentation">(‘someone is in a <span dir="ltr" style="left: calc(var(--scale-factor)*228.22px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999729);" role="presentation">predicament, has no choice’), <span dir="ltr" style="left: calc(var(--scale-factor)*348.53px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.972085);" role="presentation">ktoś ma z <span dir="ltr" style="left: calc(var(--scale-factor)*388.11px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.957326);" role="presentation">kimś <span dir="ltr" style="left: calc(var(--scale-factor)*66.20px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08093);" role="presentation">na <span dir="ltr" style="left: calc(var(--scale-factor)*78.22px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.985592);" role="presentation">pieńku <span dir="ltr" style="left: calc(var(--scale-factor)*106.86px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.974884);" role="presentation">(‘someone wants to <span dir="ltr" style="left: calc(var(--scale-factor)*185.02px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.998164);" role="presentation">complain about something to <span dir="ltr" style="left: calc(var(--scale-factor)*303.01px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.989143);" role="presentation">somebody, someone bears a <span dir="ltr" style="left: calc(var(--scale-factor)*73.84px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02189);" role="presentation">grudge against someone) and <span dir="ltr" style="left: calc(var(--scale-factor)*196.26px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.970265);" role="presentation">ktoś gra pierwsze skrzypce <span dir="ltr" style="left: calc(var(--scale-factor)*304.02px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999902);" role="presentation">(‘someone controls, leads <span dir="ltr" style="left: calc(var(--scale-factor)*66.36px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00822);" role="presentation">or makes decisions’). Eventually, new phrasemes appeared due to <span dir="ltr" style="left: calc(var(--scale-factor)*334.01px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03061);" role="presentation">the enrichment of <span dir="ltr" style="left: calc(var(--scale-factor)*66.31px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.04618);" role="presentation">meaning of the units and modification <span dir="ltr" style="left: calc(var(--scale-factor)*228.88px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03046);" role="presentation">of their semantic and selective valency: <span dir="ltr" style="left: calc(var(--scale-factor)*394.75px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.897913);" role="presentation">coś <span dir="ltr" style="left: calc(var(--scale-factor)*66.28px); top: calc(var(--scale-factor)*286.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.932543);" role="presentation">leży i <span dir="ltr" style="left: calc(var(--scale-factor)*89.17px); top: calc(var(--scale-factor)*286.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.936253);" role="presentation">kwiczy <span dir="ltr" style="left: calc(var(--scale-factor)*118.64px); top: calc(var(--scale-factor)*286.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00169);" role="presentation">(‘something does not work, neither develops nor evolves, does not meet <span dir="ltr" style="left: calc(var(--scale-factor)*66.27px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03135);" role="presentation">requirements or expectations’), <span dir="ltr" style="left: calc(var(--scale-factor)*197.91px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02492);" role="presentation">ktoś ma z <span dir="ltr" style="left: calc(var(--scale-factor)*240.25px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00888);" role="presentation">czymś na <span dir="ltr" style="left: calc(var(--scale-factor)*281.12px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00313);" role="presentation">pieńku <span dir="ltr" style="left: calc(var(--scale-factor)*311.49px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02703);" role="presentation">(‘someone does not fol<span dir="ltr" style="left: calc(var(--scale-factor)*66.28px); top: calc(var(--scale-factor)*314.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01303);" role="presentation">low the rules, does not act accordingly or acceptably’) and <span dir="ltr" style="left: calc(var(--scale-factor)*305.97px); top: calc(var(--scale-factor)*314.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.959381);" role="presentation">coś gra pierwsze skrzypce <span dir="ltr" style="left: calc(var(--scale-factor)*65.74px); top: calc(var(--scale-factor)*328.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00196);" role="presentation">(‘something is most important or dominating, something is in a <span dir="ltr" style="left: calc(var(--scale-factor)*321.19px); top: calc(var(--scale-factor)*328.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.992584);" role="presentation">controlling position’). <span dir="ltr" style="left: calc(var(--scale-factor)*65.77px); top: calc(var(--scale-factor)*342.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.984499);" role="presentation">The research proved that the process of the appearance of these lexical units was facili<span dir="ltr" style="left: calc(var(--scale-factor)*66.32px); top: calc(var(--scale-factor)*356.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.992486);" role="presentation">tated by <span dir="ltr" style="left: calc(var(--scale-factor)*100.20px); top: calc(var(--scale-factor)*356.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.981115);" role="presentation">the language users’ tendency to <span dir="ltr" style="left: calc(var(--scale-factor)*226.10px); top: calc(var(--scale-factor)*356.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999632);" role="presentation">forget the motivation <span dir="ltr" style="left: calc(var(--scale-factor)*312.52px); top: calc(var(--scale-factor)*356.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.997521);" role="presentation">of the units and the evo- <span dir="ltr" style="left: calc(var(--scale-factor)*66.28px); top: calc(var(--scale-factor)*370.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02742);" role="presentation">lution <span dir="ltr" style="left: calc(var(--scale-factor)*93.19px); top: calc(var(--scale-factor)*370.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01971);" role="presentation">of their semantics towards the content which would enable connectivity <span dir="ltr" style="left: calc(var(--scale-factor)*388.65px); top: calc(var(--scale-factor)*370.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01125);" role="presentation">with <span dir="ltr" style="left: calc(var(--scale-factor)*66.29px); top: calc(var(--scale-factor)*384.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01512);" role="presentation">impersonal nouns.